2002
DOI: 10.1016/s0378-1127(01)00553-9
|View full text |Cite
|
Sign up to set email alerts
|

Stand age and habitat influences on salamanders in Appalachian cove hardwood forests

Abstract: We surveyed cove hardwood stands aged 15, 25, 50, and 285 years following clearcutting in the southern Appalachian Mountains of northem Georgia to assess the effects of stand age and stand habitat characteristics on salamander communities using drift-fence array and pitfall methodologies from May 1994 to April 1995. Over a 60,060 pitfall trapnight effort, we collected 3937 salamanders represented by Desmognathus aeneus, Desmognathus mtznticola, Desmognathus ocoee, Ilesmognathus quadramaculatus, Eurycea bisline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
(33 reference statements)
1
34
0
Order By: Relevance
“…Species preferences for light infiltration, solar radiation, and temperature regimes differ [47,122]. Although some species are sensitive to changes in these parameters, others may benefit from the manipulation and alteration of riparian vegetation [123].…”
Section: Streamside Management Zonesmentioning
confidence: 99%
“…Species preferences for light infiltration, solar radiation, and temperature regimes differ [47,122]. Although some species are sensitive to changes in these parameters, others may benefit from the manipulation and alteration of riparian vegetation [123].…”
Section: Streamside Management Zonesmentioning
confidence: 99%
“…15 landscape-level a priori models were developed using 14 GIS-derived covariates (Table 3). For both sets of models, covariates were grouped based on biologically relevant information or recommendations from available literature (Petranka et al, 1993;Ford et al, 2002;Willson and Dorcas, 2003;Moseley et al, 2008). All combinations of the parameters were not considered as this would have created unreliable outputs (Burnham and Anderson, 2002).…”
Section: Model Selectionmentioning
confidence: 99%
“…In the eastern United States, majority of this work has focused on the effects of forestry practices in relation to salamander abundances. In the central and southern Appalachians, data suggest forestry practices at the stand and landscape scale, at least in the short-term, lead to declines in terrestrial salamander abundance until sufficient forest maturation occurs (Ash, 1988;Petranka et al, 1993;Harper and Guynn, 1999;Ford et al, 2002). At smaller spatial scales, logging-related alterations to riparian quality (reduced canopy cover, leaf litter depth and decreased soil moisture) along with the alteration of physical stream conditions (change in stream substrate class, substrate embeddedness, riffle/run/pool composition) negatively influence stream salamander populations (Crawford and Semlitsch, 2008;Moseley et al, 2008;Peterman and Semlitsch, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Past research supports the use of salamander abundances and body condition as indicators of seral advancement. Their numbers increase along advancing seral continua in multiple temperate forest types in North America (e.g., Welsh and Lind 1991, Cooperrider et al 2000, Ford et al 2002, Homyack and Haas 2009, and body condition has been shown to differ with varying forest management (e.g., Karraker andWelsh 2006, Welsh et al 2008).…”
Section: Introductionmentioning
confidence: 99%